EXAMINING THE ANTECEDENTS OF LEARNING AGILITY: A STUDY OF TRANSFORMATIVE LEARNING AND ADAPTIVE PERFORMANCE AMONG SEMARANG LECTURERS - Wea, Donatus; Amsar, Amsar (Jurnal Ekonomi, 2023)
This research examines the relationship between learning culture, transformative learning, learning agility, work engagement, and adaptive performance among private university lecturers in Semarang. Using a quantitative approach with a sample of 184 respondents, this study applies Structural Equation Modeling (SEM) for data analysis. The research results show a significant relationship between the variables studied. Learning culture has a positive effect on transformative learning and work engagement. Transformative learning and learning agility contribute significantly to adaptive performance. These findings emphasize the importance of transformative learning in increasing learning agility and adaptive performance of lecturers. This study provides valuable insight for developing strategies for improving lecturers' adaptive performance in facing the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. Future research is recommended to expand the scope and use a longitudinal approach for a more comprehensive understanding